2002
DOI: 10.1128/iai.70.8.3994-4001.2002
|View full text |Cite
|
Sign up to set email alerts
|

LeishmaniaPriming of Human Dendritic Cells for CD40 Ligand-Induced Interleukin-12p70 Secretion Is Strain and Species Dependent

Abstract: A major question in the study of leishmaniasis is what dictates clinical disease expression produced by different Leishmania species, i.e., cutaneous versus systemic and healing versus nonhealing. Animal models using a Leishmania species associated with self-limiting cutaneous disease (L. major) have revealed that protective immunity requires CD40/CD40 ligand (CD40L)-dependent, interleukin-12 (IL-12)-driven Th1 responses. We recently showed that L. major can prime human dendritic cells (DCs) for CD40L-triggere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
88
3
11

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(115 citation statements)
references
References 58 publications
13
88
3
11
Order By: Relevance
“…This is evidenced by several observations showing that disruption of the CD40-CD40L costimulatory pathway reduces IL-12 production and reverses the normal healing pattern of an L. major infection in a resistant strain of mouse (21,22). In addition, recent studies have shown that infection-induced IL-12 production by Leishmania-infected DCs requires additional signaling through the CD40-CD40L pathway (20,19).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This is evidenced by several observations showing that disruption of the CD40-CD40L costimulatory pathway reduces IL-12 production and reverses the normal healing pattern of an L. major infection in a resistant strain of mouse (21,22). In addition, recent studies have shown that infection-induced IL-12 production by Leishmania-infected DCs requires additional signaling through the CD40-CD40L pathway (20,19).…”
Section: Discussionmentioning
confidence: 89%
“…Still, direct infection is not always a sufficient stimulus to induce production of this cytokine as evidenced by the observation that infection of human myeloid DCs with L. major failed to directly induce IL-12 production, although infection did up-regulate levels of MHC class II and costimulatory molecules. However, following interaction with CD40 ligand, infected DCs did produce increased levels IL-12p70 over that produced by uninfected DCs (19) although the capacity to stimulate IL-12 production varied depending on the species or strain of Leishmania used to stimulate cells (20). The concept that CD40-CD40L interactions provide a necessary stimulus for IL-12 production during cutaneous leishmaniasis is strongly supported by in vivo studies showing that CD40 (21) and CD40L (22,23) deficient mice as well as mice treated with neutralizing anti-CD40L Ab (24) fail to develop a protective cell mediated immune response following infection with L. major and the related protozoan parasite, Leishmania amazonensis.…”
Section: R Esistance To Leishmania Major In Mice Requires the Activatmentioning
confidence: 99%
“…infection is likely dendritic cells (Gorak et al, 1998;Marovich et al, 2000;McDowell et al, 2002). However, Leishmania spp.-infected dendritic cells require CD40L costimulation for IL-12 production (Marovich et al, 2000;McDowell et al, 2002), suggesting that during infection, dendritic cells initiate a protective response after interaction with antigenspecific T-cells in lymphoid tissue. For parasites that normally target MP for survival, the avoidance of IL-12 early during infection would serve as an adaptive strategy to establish an infection.…”
Section: Discussionmentioning
confidence: 99%
“…Infection by Leishmania tropica and Leishmania donovani results in nonhealing cutaneous and severe visceral forms of leishmaniasis, respectively. These two species are deficient in the ability to prime DCs for CD40L-dependent IL-12 production relative to Leishmania major, which causes a less severe form of cutaneous disease (34).…”
Section: Discussionmentioning
confidence: 99%